Shinto shrines : a guide to the sacred sites of Japan's ancient religion - Cali, Joseph; Dougill, John (University of Hawaiʻi Press, 2013)
Of Japan's two great religious traditions, Shinto is far less known and understood in the West. Although there are a number of books that explain the religion and its philosophy, this work is the first in English to focus on sites where Shinto has been practiced since the dawn of Japanese history. In an extensive introductory section, the authors delve into the fascinating aspects of Shinto, clarifying its relationship with Buddhism as well as its customs, symbolism, and pilgrimage routes. This is followed by a fully illustrated guide to 57 major Shinto shrines throughout Japan, many of which have been designated World Heritage Sites or National Treasures. In each comprehensive entry, the authors highlight important spiritual and physical features of the individual shrines (architecture, design, and art), associated festivals, and enshrined gods. They note the prayers offered and, for travelers, the best times to visit. With over 125 color photographs and 50 detailed illustrations of archetypical Shinto objects and shrines, this volume will appeal not only to those interested in religion but also to armchair travelers and visitors to Japan alike.